Роль оценки в дистантном обучении - Ковальчук, ІННА (My University, 2020)
. The article examines the role of students' knowledge assessment in distance learning. Analyzing the pedagogical heritage of the past and modern works devoted to the problem of assessing student success, the author comes to the conclusion that assessment in distance learning plays a stimulating and motivational role. Emphasizes the importance of using the practice of different types of assessment and assessment methods.
Keywords: оценка, дистантное образование, ученики